Evaluating invasion risk for freshwater fishes in South Africa - Marr, S.M.; Ellender, B.R.; Woodford, D.J.; Alexander, M.E.; Wasserman, R.J.; Ivey, P.; Zengeya, T.; Weyl, O.L.F. (National Botanical Institute/AOSIS, 2017)
South Africa, as a signatory of the Convention on Biological Diversity, has an obligation to identify, prioritise and manage invasive species and their introduction pathways. However, this requires knowledge of the introduction pathways, factors influencing establishment success, invasive potential, current distributions and ecological impacts. Objectives: To evaluate the Fish Invasiveness Screening Kit (FISK) to predict the invasion risk posed by fish species proposed for introduction into South Africa. Method: FISK assessments were compiled for species whose invasion status in South Africa was known. A Receiver operating characteristic (ROC) analysis was conducted to calibrate the FISK for South Africa. The calibrated FISK was used to evaluate the risk that three species recently proposed for importation for aquaculture could become invasive in South Africa. Results: A FISK score of 14 was identified as the threshold to delineate between species that could become invasive in South Africa and those that are unlikely to become invasive. Of the three species evaluated, Silurus glanis had a high risk of becoming invasive in South Africa, Lates calcarifer was likely to be invasive and Oncorhynchus tshawytscha was unlikely to be invasive in South Africa. Conclusion: FISK was demonstrated to be a useful risk assessment tool to evaluate the invasion risk posed by species proposed for use in aquaculture. For the large number of fish imported for the pet trade, a rapid screening assessment to flag potentially high risk species was recommended prior to a full FISK assessment for flagged species.
Keywords: freshwater; fish; south africa; invasion risk